Perfil semântico da sala de aula de ciências - Pinto, Bruna Cristina Nunes (2021)
The present study sought to analyze the semantic profiles present in the dialogical interactions in the classroom of a class of 7th grade of Elementary School, in which the application of Conversation Wheels guided by the FA²IA methodology occurred. To collect the data, audio and video capture resources were used. In order to promote the construction of semantic waves, the data analysis took place through the use of semantic levels, they are: Semantic Density and Semantic Gravity, both derived from the Legitimation Code Theory with some elements of Axiology. As a result, it was identified that the Conversation Wheels, as they were structured and developed, did not allow the construction of semantic waves, both in relation to gravity and in relation to density, even with strong dialogical interactions between students and between students and the teacher, however it was possible to observe how the values are inserted in the relationships in the classroom.